Using chiral ionic liquid additives to enhance asymmetric induction in a Diels–Alder reaction. Issue 5 (19th January 2017) - Goodrich, P.; Nimal Gunaratne, H. Q.; Hall, L.; Wang, Y.; Jin, L.; Muldoon, M. J.; Ribeiro, A. P. C.; Pombeiro, A. J. L.; Pârvulescu, V. I.; Davey, P.; Hardacre, C.
Abstract : A bis-oxazoline ligand has been complexed using Cu(ii ) and Zn(ii ) trifluoromethanesulfonate and a range of chiral ionic liquid (CIL) additives based on natural products were used as a co-catalyst for a Diels–Alder reaction. Abstract : A bis-oxazoline ligand has been complexed using Cu(ii ) and Zn(ii ) trifluoromethanesulfonate and a range of chiral ionic liquid (CIL) additives based on natural products were used as a co-catalyst for a Diels–Alder reaction. The catalytic performance of these systems was compared for the asymmetric Diels–Alder reaction between N -acryloyloxazolidinone and cyclopentadiene with and without the presence of a CIL additive. In the absence of the CIL, both catalysts resulted in low enantioselectivities in conventional solvents and ionic liquids. However, whilst only a minor effect of the CIL was observed for the Cu based catalyst, in the case of the Zn based catalyst, significant enhancements in endo enantioselectivity of up to 50% were found on the addition of a CIL.